PENYELESAIAN SENGKETA CACAT OBJEK SERTIFIKAT DENGAN PERBEDAAN PADA PETA AGRARIA DAN TATA RUANG - Timisela, Retsky (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2025)
This study was conducted to analyze the differences in the area of objects listed on the certificate and the area of objects listed on the Agrarian and Spatial Planning map. Based on the reality that occurs in the process of issuing land certificates or buying and selling land where sometimes the area of objects listed on the certificate does not match that listed on the Agrarian and Spatial Planning map. The purpose of this study was to analyze, discuss and understand the certificate of proof of rights in order to obtain legal certainty. In this study, a normative juridical method was used, namely a method based on primary legal materials such as laws, theories, concepts, and legal principles. And using an empirical normative method that focuses on data, real evidence, and measurable facts on the disputed object to be observed.